2019
DOI: 10.1200/jco.2019.37.15_suppl.e17030
|View full text |Cite
|
Sign up to set email alerts
|

Sarcopenia as a predictor of survival in patients with epithelial ovarian cancer (EOC) receiving platinum and taxane-based chemotherapy.

Abstract: e17030 Background: Severe skeletal muscle loss (sarcopenia) is associated with poor cancer outcomes, including reduced survival and increased treatment toxicity. This relationship has recently been demonstrated in women with metastatic breast cancer, but there is a paucity of data regarding this correlation in women with EOC. Thus, our goal was to evaluate if sarcopenia, as assessed by computed tomography (CT) morphometric measurements, was associated with worse survival outcomes in EOC patients undergoing pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Previous studies have suggested sarcopenia as a prognostic factor associated with poor survival and increased resistance and toxicity to chemotherapy in patients with various malignancies, including breast, small cell lung, urothelial, and gastric cancers [5][6][7][8]. In ovarian cancer, conflicting results have been reported: while some studies concluded that sarcopenia adversely affected patients' progression-free survival (PFS) or overall survival (OS) [9,10], others could not determine a significant association of sarcopenia with survival outcomes [11,12]. There were differences in study design, population, disease setting, and definition of sarcopenia among the studies; therefore, careful attention is required to interpret the study results.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have suggested sarcopenia as a prognostic factor associated with poor survival and increased resistance and toxicity to chemotherapy in patients with various malignancies, including breast, small cell lung, urothelial, and gastric cancers [5][6][7][8]. In ovarian cancer, conflicting results have been reported: while some studies concluded that sarcopenia adversely affected patients' progression-free survival (PFS) or overall survival (OS) [9,10], others could not determine a significant association of sarcopenia with survival outcomes [11,12]. There were differences in study design, population, disease setting, and definition of sarcopenia among the studies; therefore, careful attention is required to interpret the study results.…”
Section: Introductionmentioning
confidence: 99%